2012
DOI: 10.1186/2110-5820-2-40
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of an early cooling phase in continuous renal replacement therapy for ICU patients

Abstract: BackgroundLowering the temperature setting in the heating device during continuous venovenous hemofiltration (CVVH) is an option. The purpose of this study was to determine the effects on body temperature and hemodynamic tolerance of two different temperature settings in the warming device in patients treated with CVVH.MethodsThirty patients (mean age: 66.5 years; mean SAPS 2: 55) were enrolled in a prospective crossover randomized study. After a baseline of 2 h at 38°C, the heating device was randomly set to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Bellomo et al, found that the average pH and bicarbonate levels increased 0.075 and 4.5 mmol/l [26] , respectively, similar to our cohort in whom pH and bicarbonate increased 0.022 and 4 mmol/l, respectively. Robert et al reported that the mean temperature decreased by 1.05 ° C during CRRT (vs. 1.7 ° C in our report) [39] . Graham et al, described fewer catheter-related blood stream infections (0.03 vs. 1.2%/day), more pneumothoraces (2.4% vs. none), more hemothoraces (0.4% vs. none) and a similar arterial puncture rate (0.09 vs. 0.1%) [31] .…”
Section: Discussionmentioning
confidence: 57%
“…Bellomo et al, found that the average pH and bicarbonate levels increased 0.075 and 4.5 mmol/l [26] , respectively, similar to our cohort in whom pH and bicarbonate increased 0.022 and 4 mmol/l, respectively. Robert et al reported that the mean temperature decreased by 1.05 ° C during CRRT (vs. 1.7 ° C in our report) [39] . Graham et al, described fewer catheter-related blood stream infections (0.03 vs. 1.2%/day), more pneumothoraces (2.4% vs. none), more hemothoraces (0.4% vs. none) and a similar arterial puncture rate (0.09 vs. 0.1%) [31] .…”
Section: Discussionmentioning
confidence: 57%
“…Ideally, the dialysate temperature should be tailored to the pre‐dialysis body temperature of the individual patient . In patients prone to hypotension on hemodialysis, lowering of dialysate temperature improves hemodynamic tolerance of HD …”
Section: Thermal Balance In Extracorporeal Therapiesmentioning
confidence: 99%
“…If the incorporated CRRT heating system fails to maintain the desired core temperature, external heating aiming at a temperature above 37°C (and sometimes even close to 42°C) must be utilized [32]. Of note, cooling may beneficially affect hemodynamics and outcome in ICU patients [33]. As such, CRRT has proven useful to quickly establish hypothermia in certain conditions (e.g.…”
Section: Heat and Energy Lossmentioning
confidence: 99%
“…On the contrary, and especially during shock, overzealous hypothermia may be deleterious for myocardial function and should be carefully monitored especially also regarding clothing and platelet count [33,34]. Ideally, energy requirements should be measured by indirect calorimetry to more correctly match the amount of delivered calories to the patient's needs [35].…”
Section: Heat and Energy Lossmentioning
confidence: 99%
See 1 more Smart Citation